ORGANIZING FORMS OF COURSES THROUGH INTERNATIONAL EDUCATIONAL PROGRAMS BASED ON THE EXPERIENCE OF DEVELOPED COUNTRIES (British Journal of Global Ecology and Sustainable Development, 2023)
This article discusses the current reforms in the education system, their effective results, the study of the experience of countries that have successfully participated in international research, the use of modern pedagogical technologies in teaching, new approaches to teaching referred to.